Beef production and ecosystem services in Canada's prairie provinces: A review. (October 2018) - Pogue, Sarah J.; Kröbel, Roland; Janzen, H. Henry; Beauchemin, Karen A.; Legesse, Getahun; de Souza, Danielle Maia; Iravani, Majid; Selin, Carrie; Byrne, James; McAllister, Tim A.
Abstract: Globally, consumption of bovine meat is projected to increase by 1.2% per annum until 2050, a demand likely met in part by increased Canadian beef production. With this greater production on a finite agricultural land base, there is a need to weigh the contribution of this industry to the Canadian economy against the full range of positive and negative ecological and social impacts of beef production. This review, focussing on the prairie provinces of Alberta, Saskatchewan and Manitoba, which collectively support just over 80% of the Canadian beef herd, examines the social and ecological footprint of the cow-calf, backgrounding, finishing and forage/feed production stages of beef production within an ecosystem services framework. We summarise the literature on how beef production and management practices affect a range of services, including livestock; water supply; water, air and soil quality; climate regulation; zoonotic diseases; cultural services; and biodiversity. Based on 742 peer-reviewed publications, spanning all agricultural stages of beef production, we established a framework for identifying management practices yielding the greatest overall socio-ecological benefits in terms of positive impacts on ecosystem service supply. Further, we identified research gaps and crucial research questions related to the sustainability of beef production systems. Highlights: 742 publications on prairie beef production and ecosystem services were reviewed. Beef management practices influence the supply of services from the system. There is relatively little research on cultural services and service bundles. Holistic assessment includes multiple production stages, practices and services.